Desempenho aerodinâmico das pás de um aerogerador de pequeno porte, perfil NREL S809, em diferentes velocidades específicas de projeto - Silva, Daniel Paixão da (2012)
The blades of a wind turbine are the direct component in the conversion of the kinetic energy of the wind into rotational energy. The blades have the operating principle based on the action of aerodynamic forces on their profiles, producing a torque on the axis of rotation, which is captured by a generator and thus transformed into electrical energy. In the energy conversion process there are both mechanical and electrical losses and by that the blades must be designed to be the most efficient in the operating regime where they are used. The present work aims at testing the aerodynamic performance of a set of turbine blades, 1.5 m radius, using NREL S809 airfoil and designed based on the Blade Element Momentum Theory (BEM). The results, expressed by the characteristic curves showed that among the tested blades, l = 7 had the best performance, obtaining a value of Cpmax = 0.31.